2018
DOI: 10.1097/mrr.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Walking endurance and perceived symptom severity after a single maximal exercise test in persons with mild disability because of multiple sclerosis

Abstract: People with multiple sclerosis (PwMS) are less physically active compared with the general population. This might also be because of the perception of temporary worsening of symptoms during physical activity. Forty-two PwMS with a mild level of disability underwent a maximal exercise test on a bicycle ergometer. Fifteen minutes before and 15 and 75 min after the maximal exercise test, the 6-minute walking test was conducted and the rate of perceived exertion was recorded. Twice before and three times after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Previous research has also demonstrated improved mobility after an acute bout of exercise. Moumdjian et al 10 found improved walking endurance in participants with MS after bicycle ergometry regardless of perceived worsening of balance and gait symptoms. These researchers suggested that the exercise may have promoted changes in gait quality even with perceived decrements in gait pattern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has also demonstrated improved mobility after an acute bout of exercise. Moumdjian et al 10 found improved walking endurance in participants with MS after bicycle ergometry regardless of perceived worsening of balance and gait symptoms. These researchers suggested that the exercise may have promoted changes in gait quality even with perceived decrements in gait pattern.…”
Section: Discussionmentioning
confidence: 99%
“…11 There is also evidence showing that in one session of bicycle ergometry, in which perceived decrements in balance and gait were reported, walking endurance actually improved. 10 Although such findings are promising in terms of the utility of exercise as a prescriptive health treatment modality, the findings are limited by considering symptoms as a composite measure rather than separate symptom domains or by examining only changes in the perception of these balance and mobility changes rather than objectively measured changes. For those with MS, instrumented measures of standing balance and gait have been shown to be more sensitive in detecting subtle gait deficits in the absence of clinical manifestation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SOB may have inhibited exercise in cirrhosis population because this symptom becomes worse during exercise. Patients who perceive a temporary worsening of symptoms during physical activity may be less physically active [20].…”
Section: Discussionmentioning
confidence: 99%
“…SOB may have inhibited exercise in the cirrhosis patient population because this symptom becomes worse during exercise. Patients who perceive a temporary worsening of symptoms during physical activity may be less physically active [30]. Previous studies of the relationship between dyspnea and exercise intolerance were conducted in patients with pulmonary disease and multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%